2002
DOI: 10.1093/tropej/48.2.109
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive Breastfeeding is Undermined by Use of Other Liquids in Rural Southwestern Nigeria

Abstract: Exclusive breastfeeding (EBF) requires that the child be started on breastmilk on the first day of life and to continue with breastmilk alone for the next 4-6 months. EBF is compromised even when water is given to a child. This study surveyed the breastfeeding practices and opinions of 411 mothers of children aged 4-28 months in the rural community of Igbo-Ora in southwestern Nigeria. While all children were given breastmilk throughout that period, all received plain water during the first week of life. Herbal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 0 publications
3
29
0
Order By: Relevance
“…In addition, Sachdev et al (1991) and Nwankwo and Brieger (2002) reported that health workers advised mothers to give water or glucose water to new-borns. Such beliefs and advice were contrary to WHO and UNICEF recommendations.…”
Section: Infant and Maternal Characteristicsmentioning
confidence: 99%
“…In addition, Sachdev et al (1991) and Nwankwo and Brieger (2002) reported that health workers advised mothers to give water or glucose water to new-borns. Such beliefs and advice were contrary to WHO and UNICEF recommendations.…”
Section: Infant and Maternal Characteristicsmentioning
confidence: 99%
“…A few mothers had stopped breastfeeding probably because they had a lactation failure, not enough milk, engorged breasts, sore nipples, sickness and a busy employment schedule which involved traveling [21]. Such possibilities have been proven from studies in Nigeria where complementary foods are introduced due to perceived lactation inefficiency [21,22]. However, mothers in developing countries introduce complementary feeding for many reasons.…”
Section: Prevalence Of Anaemia and Idamentioning
confidence: 99%
“…However, mothers in developing countries introduce complementary feeding for many reasons. In Nigeria few infants are exclusively breastfed but instead they are given alternative feeds like water, formula and herbal tea from an early age [21]. In a Malawian study, only 19% of the infants in a cohort of 720 were exclusively breastfed for the first six months in their first year of life [22].…”
Section: Prevalence Of Anaemia and Idamentioning
confidence: 99%
See 1 more Smart Citation
“…This decline was attributed to several factors. One of this was that mothers had the perception that exclusive breastfeeding was 'physically draining' on them (Nwankwo and Brieger, 2002;Naanyu, 2010). The energy cost of lactation is generally considered to represent a substantial drain on maternal nutritional metabolism (Lunn, 1996).…”
Section: Introductionmentioning
confidence: 99%